Confiança na comunicação de informações econômico-financeiras: o caso das empresas de autogestão - Morgado, Flávio (2008)
After the financial scandals which occurred in 2001, when confidence in the financial market has been questioned, the issue of corporate governance has become part of the agenda of the shareholders and stakeholders - corporate customers and suppliers, government and individual investors, pension funds and society in general - especially with the financial statements and the audit to which they were submitted. The financial statements can be considered expert systems, which are systems of technical excellence and professional competence on which we do not know and we can t give most of the reasons (codes of knowledge) governing its operation. It s taken for granted; there is faith, not so much in their competences, but the authenticity of expert knowledge, based on experience and regularity in the operation of these systems, in addition to the regulatory forces, which aim at protecting users. The objective of this work is to establish criteria for the creation of confidence in the communication process of economic-financial information. The research is inserted in the field of organizational communication. The methodology used was that of multiple case studies, involving the components of the accounting communication process in self management enterprises. The sender, the message and channel were evaluated for reliability (be worthy of trust). The receiver was evaluated as to the trust (the act of trust). The results showed the importance of transparency in the dissemination of information, combined with effective internal controls as a requirement for self management and for internal democracy. The also showed the difficulties of workers in self management enterprises, of knowing about management, undermining thus the question of participation. Another observation is that trust is also the product of self-management and institutional environment for Solidarity Economy which has the confidence as a principle